Indeks Keanekragaman Hasil Tangkapan Jaring Insang Hanyut (Drift Gillnet) Di Kelurahan Sei Berombang Kecamatan Panai Hilir Kabupaten Labuhan Batu Sumatera Utara - Eka Anjar Sari Nasution; Yun Alwi; Rizky Janatul Magwa; Nurhayati Nurhayati; Fauzan Ramadan; Muhammad Hariski (Universitas Mataram, 2024)
Sei Berombang Village has significant potential natural resources in the fisheries sector. The waters of Sei Berombang Village are estuarine, where river water mixes with seawater. The fishing gear used in the study at Sei Berombang Village was a drift gillnet with a mesh size of 2 inches and a boat size of 3 GT. The research was conducted from January 8 to February 5, 2024, in the waters of Sei Berombang Village. This study aimed to determine the species diversity of fish caught by drift gillnets. The research used survey and observation methods. Data analysis included catch composition, diversity index, evenness index, and dominance index. The results showed that the catch using drift gillnets in the waters of Sei Berombang Village consisted of 15 species. The primary catch by drift gillnets, from highest to lowest, included pomfret with 1,001 individuals (19.81%) and the lowest being mullet with 375 individuals (7.42%). The highest bycatch was sweet shrimp with 714 individuals (14.13%), and the lowest was crab with 36 individuals (0.71%). The highest discard was pufferfish with 120 individuals (2.37%), and the lowest was baji fish with 5 individuals (0.1%), with the total catch weighing 541.5 kg and the total number of catches being 5,053 individuals. The obtained diversity index was 2.39, categorized as moderate; the evenness index was 0.88, categorized as high; and the dominance index was 0.11, categorized as low.